Permanent Pacemaker Use in Transcatheter Aortic Valve Replacement: Real World Experience from the National Inpatient Sample - Muthu Krishnan, Anand; Kadavath, Sabeeda; Kowlgi, Gurukripa; Goel, Akshay; Wu, Fangcheng; Jha, Anil; Correa De Sa, Daniel; Lahoud, Rony (International Journal of Clinical Research, 2023)
Background: Transcatheter Aortic Valve Replacement (TAVR) is associated with conduction abnormalities requiring permanent pacemaker implantation (PPMI). Data regarding predictors for PPMI following TAVR is scarce. Methods: This is a retrospective study utilizing the 2017 National In-Patient Sample (NIS). Patients who underwent TAVR and PPMI during the same admission were identified using appropriate ICD-10 codes, as were patients with left bundle branch (LBBB), right bundle branch (RBBB), and first-degree AV delay (AVB). Patients were split into two groups based on PPMI. The groups were compared using univariate and multivariate analyses after adjusting for age, gender, race, comorbidities, insurance status, and Charlson comorbidity index (CCI). Secondary outcomes included factors influencing length of stay (LOS) and total charges incurred. Results: In 2017, 54,175 (57.6% males) patients underwent TAVR. There were 8,067 patients with LBBB, 2,402 with RBBB, and 2,905 with AVB at baseline. A 4170 total of patients (55.2% males) required PPMI. Patients requiring PPMI were older (80.5 vs 79.6 years, p=0.001). On multivariate analyses, baseline RBBB, LBBB, hypertension (HTN), CCI 2, and CCI >/=3 predicted PPMI (aOR 4.82, p<0.001; aOR 1.63, p<0.001; aOR 1.21, p=0.013, aOR 1.53, p=0.022 and aOR 1.46, p=0.031 respectively). On multivariate analyses, patients who underwent PPMI had significantly higher LOS (aOR 2.18, p<0.001) and incurred higher total charges (USD 278,000 vs USD 204,920; p<0.001). Conclusion: In this cohort, RBBB, LBBB, HTN, and increased CCI predicted PPMI after TAVR. Further studies are required to corroborate our findings.